Teknologi sebagai Media Komunikasi Interaktif dalam Pendidikan Agama Kristen - Mick R. Manuahe, Yani (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2024)
Christian religious education plays a crucial role in transmitting Christian values to the younger generation. In this context, communication holds a central role in the process of Christian religious education, encompassing the presentation of material, the flow of discussions, and the reflective processes. Interactive communication emerges as a key element in Christian religious education, where the process refers to the active interaction between the communicator (teacher) and the communicatee (student). Technology has become an integral part of social and educational life. In Christian religious education, the utilization of technology as a tool for interactive communication can enhance student engagement and the effectiveness of material delivery. This research aims to evaluate the role of technology as a medium for interactive communication in the context of Christian religious education. The applied research method is a literature review, enabling the researcher to construct a robust theoretical foundation based on relevant literature in the field. With this approach, it is expected to form a deeper understanding of the contribution of technology in enriching interactive communication in Christian religious education.